Relativism and intolerance, two sides of a coin: Qur’ānic exposition - Bahari, Che Amnah (IIUM Journal Publication Unit, 2020)
Numerous catastrophic consequences have been attributed to ethical relativism, ranging from increased crime rates due to intolerance to the decline of social values as the result of not understanding tolerance. Although doubting some reports on the about such empirical claims, this paper contends that relativism has dissident explanatory outcome. Concentrating on the library research and finding, the focus of the outcome is its disloyalty to ethical understanding which in turn undermines (i) reason and (ii) the idea of moral progress. In clarifying point (i), an analysis on Qur’ānic view of the term birr will be referred to the effect that Islamic ethics or akhlāq can nurture character of tolerant people who live in harmonious spirit parallel to the needs of society and the environment. In discussing the outcome of point (ii), anti-relativism is differentiated by the concept of western chauvinism and Islam. The paper concludes with the suggestion that ethical relativism’s outcome leads to perdition but deliberation on Islamic principles of ethics hold water.